PCR detection of Dirofilaria immitis in Aedes aegypti and Culex pipiens from urban temperate Argentina - Vezzani, Darío (2010)
Dirofilariasis, a mosquito-borne disease of dogs caused by the nematode Dirofilaria immitis (Leidy; Spirurida: Onchocercidae), has now become a growing zoonotic concern. Based on direct microscopical observation, Aedes aegypti (L.) and Culex pipiens L. (Diptera: Culicidae) have been previously incriminated as potential vectors of D. immitis in urban temperate Argentina. In this study, an effort was made to provide evidence for this assumption by screening of mosquitoes for D. immitis infection using a polymerase chain reaction (PCR) assay. PCR primers were developed to specifically amplify the D. immitis-16S rRNA gene and to reliably detect 100th of the genomic equivalent (10 pg) of the infective third-stage larvae in mosquito pools of up to 30 individuals. Collection of mosquitoes was performed between September 2007 and April 2008 in premises known to be inhabited by D. immitis-infected dogs in Greater Buenos Aires. The final collection comprised 453 specimens belonging to 11 mosquito species of the genera Aedes, Culex, Ochlerotatus, and Psorophora. PCR assays were performed on 82 pools (n ≤ 20) of heads and abdomens separately, as this allows differentiating infective and non-infective stages of the parasite, respectively. Identification of the non-infective stage of D. immitis in A. aegypti and C. pipiens provided additional strong support of transmission of the parasite by these species. To our knowledge, this was the first PCR screening for D. immitis-infected mosquitoes in South America.